2004
DOI: 10.1111/j.1741-3737.2004.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Dollars, Dependency, and Divorce: Four Perspectives on the Role of Wives’ Income

Abstract: This article delineates and assesses the evidence for four perspectives that have guided previous research on the relationship between wives’ economic resources and marital stability. Hypotheses from these perspectives were tested using event history methods and 1980–1997 panel data for 1,704 individuals from the Marital Instability Over the Life Course study. Both wives’ dollar income and wives’ percentage of total family income served as measures of wives’ economic resources. The association between wives’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 22 publications
6
132
0
10
Order By: Relevance
“…Nonetheless, partial traditional specialization might exist if women are only secondary breadwinners. Becker's assertion that ''the gain from marriage is reduced, and hence the attractiveness of divorce is raised, by higher earning and labor force participation of married women '' (1991, p. 55) has been summarized by the various studies that have investigated this claim as the role specialization hypothesis (Schoen et al 2002), the wife's independence hypothesis (Ono 1998;Rogers 2004), the specialization and trading hypothesis (Oppenheimer 1997;Schoen et al 2002), the interdependence hypothesis (Schoen et al 2002), the ''price'' effect (Moffitt 2000), or the division of labor hypothesis (Poortman and Kalmijn 2002). All of these hypotheses suggest that, when wives have higher earnings, the propensity of both spouses to divorce increases because the interdependence between them no longer exists-i.e., the wife is no longer dependent on her husband's income and is Economic Determinants of Divorce Among Dual-Earner Couples free to leave the marriage because she can support herself-and the husband does not receive the level of household services he would expect under the assumption of full specialization.…”
Section: Women's Economic Activity As a Destabilizing Factor For Marrmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, partial traditional specialization might exist if women are only secondary breadwinners. Becker's assertion that ''the gain from marriage is reduced, and hence the attractiveness of divorce is raised, by higher earning and labor force participation of married women '' (1991, p. 55) has been summarized by the various studies that have investigated this claim as the role specialization hypothesis (Schoen et al 2002), the wife's independence hypothesis (Ono 1998;Rogers 2004), the specialization and trading hypothesis (Oppenheimer 1997;Schoen et al 2002), the interdependence hypothesis (Schoen et al 2002), the ''price'' effect (Moffitt 2000), or the division of labor hypothesis (Poortman and Kalmijn 2002). All of these hypotheses suggest that, when wives have higher earnings, the propensity of both spouses to divorce increases because the interdependence between them no longer exists-i.e., the wife is no longer dependent on her husband's income and is Economic Determinants of Divorce Among Dual-Earner Couples free to leave the marriage because she can support herself-and the husband does not receive the level of household services he would expect under the assumption of full specialization.…”
Section: Women's Economic Activity As a Destabilizing Factor For Marrmentioning
confidence: 99%
“…According to this hypothesis, equally dependent spouses, in which each of the partners generates 40 to 59 % of the family earnings, will have the highest probability of divorce, because the women in these couples have the lowest degree of commitment to marriage. In addition, according to Rogers (2004), the equal dependency hypothesis suggests that both spouses can initiate divorce, because their financial obligations to each other are weakest when their economic contributions are similar. Nonetheless, according to the role collaboration hypothesis (Rogers 2004), the equal dependency of the spouses will make marriage more stable because there is more equality between the partners; this might, however, be dependent on the gender expectations of the spouses and on perceptions of equality in marital relationships.…”
Section: Women's Economic Activity As a Destabilizing Factor For Marrmentioning
confidence: 99%
See 1 more Smart Citation
“…Risman and Johnson-Summerford (1998) confirm that the risk of divorce reached the lowest point in egalitarian unions. On the other hand, Heckert et al (1998) and Rogers (2004) found the exact opposite result, arguing that the association between wives' bargaining power as depicted by their economic resources and the likelihood of marital dissolution formed an inverted U-shaped curve.…”
Section: Conclusion and Recommendationmentioning
confidence: 79%
“…Divorce rates increase when women have higher earning power (particularly when she earns more than her husband) (Bracher et al 1993;Jalovaara 2003;Rogers 2004; but see Hoffman and Duncan 1995;Rogers and DeBoer 2001), although this may be moderated by gender ideology (Sayer and Bianchi 2000). Data from Mexico show that governmental cash transfers to mothers increase separation rates (Bobonis 2011), which provides strong evidence of the direct effect of income in this context.…”
Section: Predictions For Divorce and Remarriagementioning
confidence: 84%